A novel D-A type terpyridine-based carbazole Zn(II) complex with enhanced two-photon absorption and its bioimaging application. (September 2015) - Kong, Chengcheng; Peng, Muhua; Shen, Hong; Wang, Yiming; Zhang, Qiong; Wang, Hui; Zhang, Jun; Zhou, Hongping; Yang, Jiaxiang; Wu, Jieying; Tian, Yupeng
Abstract: A novel 2, 2′:6′, 2″-terpyridine-based ligandL and its Zn(II) complex[ZnL 2 ](PF 6 ) 2 were designed, synthesized and fully characterized. The crystal structures ofL and[ZnL 2 ](PF 6 ) 2 were confirmed by single crystal X-ray diffraction analysis. Photophysical optical properties of the ligand and its complex were investigated systemically. The results reveal that the complex exhibits a new strong absorption band at about 400 nm compared to its free ligand, which is assigned to the intramolecular charge transfer (ICT) transitions. The complex displays lower fluorescence intensity, due to the better planarity of the ligand, higher electronic mobility, and leading to easier ICT. However, two-photon absorption (2PA) cross-sections of the complex is much enhanced than that of the free ligand in the near-infrared region (NIR). Furthermore, [ZnL 2 ](PF 6 ) 2 can be penetrated into living cells without cell-penetrating molecular transporter, stained with cytoplasm in the NIR (830 nm). Therefore such complex is promising for further biomaging applications. Graphical abstract: A novel 2, 2′:6′, 2″-terpyridine-based ligandL and complex[ZnL 2 ](PF 6 ) 2 were designed, synthesized and fully characterized. The results reveal that the complex has low cytotoxicity and can be penetrated into living cells and stained with cytoplasm, so it is promising for biomaging applications. Highlights: The d 10 -metal complex with two-photon absorption (2PA) in the near-infrared region (NIR) are reported. The crystal structure ofL and[ZnL 2 ](PF 6 ) 2 was determined. The connections between structure and properties for them were investigated. The two-photon absorption (2PA) cross-sections of the complex is much enhanced than that of the free ligand. The potential application of the complex[ZnL 2 ](PF 6 ) 2 in two-photon biological imaging was evaluated.